2019
DOI: 10.1016/j.bandl.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The peri-Sylvian cortical network underlying single word repetition revealed by electrocortical stimulation and direct neural recordings

Abstract: Verbal repetition requires the coordination of auditory, memory, linguistic, and motor systems. To date, the basic dynamics of neural information processing in this deceptively simple behavior are largely unknown. Here, we examined the neural processes underlying verbal repetition using focal interruption (electrocortical stimulation) in 59 patients undergoing awake craniotomies, and neurophysiological recordings (electrocorticography) in 8 patients while they performed a single word repetition task. Electroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 66 publications
2
42
0
Order By: Relevance
“…NMF is particularly useful for decomposing data into "parts" that have interpretable meanings (e.g., transient vs sustained response types) (Lee and Seung, 1999;Donoho and Stodden, 2004;Bouchard et al, 2016;Leonard et al, 2016). The HG activity for each vSMC electrode across all participants was averaged across trials, offset by the minimum value (such that all values were positive), and NMF was applied to the matrix of time courses ϫ electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…NMF is particularly useful for decomposing data into "parts" that have interpretable meanings (e.g., transient vs sustained response types) (Lee and Seung, 1999;Donoho and Stodden, 2004;Bouchard et al, 2016;Leonard et al, 2016). The HG activity for each vSMC electrode across all participants was averaged across trials, offset by the minimum value (such that all values were positive), and NMF was applied to the matrix of time courses ϫ electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…An important goal for future research will be to understand the real-time dynamics of functional interactions between the right inferior frontal gyrus and right superior temporal gyrus when patients are repeating melodies and sentences. Future work with electrocorticography could study the dynamics that mediate interactions between the right superior temporal gyrus and right inferior frontal gyrus during melody and language processing (e.g., for evidence in the domain of language see [3133]; for review, see [3435]).…”
Section: Discussionmentioning
confidence: 99%
“…2). In this study, we focused on the HG band given its strong association with cortical activation (Ray et al, 2008) and relevance for linguistic neurophysiology (Leonard et al, 2016a; Leonard et al, 2016b; Steinschneider et al, 2011), though analysis of lower frequency dynamics would also be possible with data acquired by the RNS System. Future experiments employing a more diverse array of tasks could determine the specificity of the observed responses for language, motor preparation, or other aspects of cognitive processing (Udden and Bahlmann, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…She underwent iEEG with left frontotemporal grid electrode coverage, and ictal recordings localized seizures to the posterior left STG. Both extraoperative (during inpatient seizure monitoring) and intraoperative (during grid explantation) electrical stimulation mapping revealed that the seizure onset zone encompassed eloquent language cortex, including parts of classical Wernicke’s area (Leonard et al, 2016b). This region was deemed unresectable, so the RNS System was implanted as an alternative treatment option.…”
Section: Methodsmentioning
confidence: 99%